2023
DOI: 10.3233/bmr-210331
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of maximum joint angles during pole vaulting between male pole vaulters with and without lumbar disc degeneration or lumbar spondylolysis

Abstract: BACKGROUND: Pole vaulting involves trunk flexion, extension, and rotation, which may place the lumbar spine under stress. Repeated pole vaulting may cause lumbar disc degeneration (DD) and lumbar spondylolysis (LS); however, this phenomenon is yet to be established. OBJECTIVE: This study aimed to determine the difference in the maximum joint angles of the shoulder, hip, and trunk during pole vaulting between male pole vaulters with and without lumbar DD or LS. METHODS: This retrospective study included 17 male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…A procedure employed in a previous study (13) was used for biomechanical analysis. The video for motion analysis was recorded from four directions with the planting box at the center using four high-speed cameras (GC-LJ20B, JVC, Kanagawa, Japan), recording at a rate of 240 fields/s.…”
Section: Biomechanical Analysismentioning
confidence: 99%
“…A procedure employed in a previous study (13) was used for biomechanical analysis. The video for motion analysis was recorded from four directions with the planting box at the center using four high-speed cameras (GC-LJ20B, JVC, Kanagawa, Japan), recording at a rate of 240 fields/s.…”
Section: Biomechanical Analysismentioning
confidence: 99%
“…For the experimental trials, the vaulter performed on bungee bars that were set at 90% of their personal best record until the vaulter was able to jump over the bar three times, and those three trials were used for the analytical trials. In this study, a bungee bar was used to ensure safety and reduce the burden on the participant [9]. The mean of the three analyzed trials was used for statistical analysis.…”
Section: Biomechanical Analysismentioning
confidence: 99%
“…Motion factors (such as differences in skill level and vaulting) may cause chronic LBP [1], which has not been previously studied. A previous study reported that the maximum hip flexion angle on the TO leg during pole vaulting in the vaulters with lumbar disc degeneration was significantly smaller than that in the vaulters without lumbar disc degeneration [9]. Therefore, if the joint angles of the joints adjacent (such as shoulder or hip) to the lumbar region during pole vaulting are small, there may be increased mobility in the lumbar region.…”
Section: Introductionmentioning
confidence: 95%